Produções discursivas em campanhas publicitárias: gênero e interseccionalidades - PITANGA, Carolina Vasconcelos (2017)
This thesis has as main objective to analyze the advertising discourse as technology that produces the genre and that naturalizes and conveys an alleged truth about the sexual difference. Understanding the publicity pieces as statements, I use the analytical schemes mobilized by Michel Foucault and Judith Butler to construct the argument that the pieces transmitted by the cosmetic companies, in the scope of the open television in Brazil, have different ways of presenting markings of the difference, characterized From a binary perspective, constituting, thus, references that configure models of femininities and masculinities. The pieces analyzed were published in the period 2008 to 2017, by the cosmetics companies O Boticário and Natura, with special emphasis on the content produced for commemorative dates, such as International Women's Day, Man's Day, Valentine's Day, Mother's Day and Father's Day. With this study, I analyze the discursive strategies used in the pieces from the perspective of gender performativity (Butler, 2003) and identify what is regularity in relation to models of corporality, ideal lifestyles and "beauty" parameters.